Principles Of Actio Paulina In Bankkruptcy Regarding The Deed Of Trasfer Of Rights Made In Front Land Tittles Registrar - maryano, Maryano; Hariansah, Syafri (Faculty of Law, Universitas Pekalongan, 2024)
The legal principle of actio pauliana is the right given to creditors to request the cancellation of all acts of transfer of rights carried out by the debtor. The curator is the only party who can cancel legal actions carried out by the bankruptcy debtor based on the legal principle of actio pauliana through the Court, so that the deed of transfer of rights made by PPAT can be canceled using the legal principle of actio pauliana through a court decision. The aim of this research is to analyze the concept of the actio pauliana principle in the legal system in Indonesia and find out the legal position of the deed of transfer of rights made before the PPAT which is submitted for actio pauliana legal action in bankruptcy in Indonesia. The method used in research is normative juridical. Based on the research results, it is concluded that the concept of the actio pauliana principle in the legal system in Indonesia has been regulated in Article 1341 of the Civil Code and Articles 41 to Article 49 of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations with the aim of protecting interests of creditors from bad actions carried out by debtors. This must go through a process by filing a lawsuit with the Commercial Court to obtain a decision to cancel the transfer of property or assets to a third party. A lawsuit for the transfer of property or assets can only be directed against a party who within 1 year before the bankruptcy occurred transferred their assets. The legal status of the deed of transfer of rights made before the PPAT which is submitted for actio pauliana legal action in bankruptcy in Indonesia is binding for both parties when the transfer of rights is carried out in good faith in accordance with the provisions required in the Law.